Socio-Psychological Predictors of Indigenous and Minorities of the North, Siberia and the Far East Students' Adaptation to College (on the Example of Organizations of Secondary Vocational Education) - I.A. Baeva; A.V. Miklyaeva; J.S. Pezhemskaya; V.V. Khoroshikh (Moscow State University of Psychology and Education, 2023)
The paper presents the results of studying the resources of academic, socio-cultural and psychological adaptation of students representing indigenous peoples of the North, Siberia and the Far East to college. The sample consisted of 720 students, of which 304 people (58% girls) identify themselves as representatives of the indigenous peoples of the North and the Far East. The collection of empirical data was carried out using questionnaires (Scale of academic motivation; Questionnaire of online and offline coping; The Child and Youth Resilience Measure; Types of ethnic identity questionnaire; Scales of Psychological problems of adolescents; Methodology psychological safety of the educational environment). The adaptability of students was studied using the Scale of Socio-Cultural Adaptation; Self-assessment scales of satisfaction with various aspects of life; author's questionnaire. Regression analysis revealed invariant predictors (emotional attitude towards college, satisfaction with the educational environment of the college, adaptation to the amount of homework in the educational process) only for academic adaptation. Indicators of introjected learning motivation are also significant for predicting the success of academic adaptation of students representing the Indigenous Minorities and the Far East. The predictor of socio-cultural adaptation for the students representing the North, Siberia and the Far East nations is the level of ethno-egoism. Coping strategies and the size of the settlement predict the psychological adaptation this group students. The results obtained can contribute to the optimization of the process of socio-psychological adaptation of students-representatives the Indigenous Minorities to study in colleges.